Organization of Specialized Ophthalmo-oncological Care in Moscow - G. Sh. Arzhimatova; A. M. Andreychenko; M. Yu. Shemyakin; E. A. Salikhov (Oftalʹmologiâ)
The purpose: to examine the issue of patient routing for individuals with malignant neoplasms affecting the eye, ocular adnexa, and orbit in Moscow.Material and methods. A retrospective analysis was conducted on the incidence of patients (MGOC) aged 18– 90 years.Results. Existing organizational challenges in the management of individuals with vision-related tumors were identified and described. Specific algorithms and timelines for their implementation in cases of suspected ophthalmological oncology are presented. The actions of healthcare professionals at each stage of diagnosis and evaluation of patients with vision-related neoplasms are highlighted, emphasizing a step-by-step routing approach for this patient group.Conclusion. The development of routing algorithms for patients with ocular edema, appendages, and the orbit allows for the acceleration of the patient examination process at each stage, leading to an accurate diagnosis and the determination of appropriate patient management strategies.